“Beyond Ethnic Economy”: Religiosity, Social Entrepreneurship, and Solidarity Formation of Indonesian Migrants in Taiwan - Yuniarto, Rudolf (UI Scholars Hub, 2021)
Indonesian migrants in Taiwan have been dominated by low skilled workers who are labelled uneducated sojourners, consumptive, the misplacement of future orientation, and a minority group struggling to survive. Several individuals concern about the migrant condition, and they are so-called migrant social entrepreneurs. Through social-religious activities and interrelations with the migrant worker community, the Indonesian entrepreneurs have created solidarity for migrant workers’ to generate living conditions that are more favourable and improve their livelihoods. Three important factors shape this condition: the marginal position of second-class migrant workers-immigrants, the virtuous value of religion, and social apprehension. Thorough analysing the religious experiences of entrepreneurs and social-religious activities, this paper shows the positive effects of the relationship between business activities and religious value application, which establish the immigrant self-identity, solidarity, leadership, and collective work formation of the Indonesian migrant community in Taiwan. The primary data is based on the observation of participants’ daily business activities and in-depth interviews with Indonesian entrepreneurs from June to December 2014. The ethnographic research method is applied as a means to explore the effect that migrant-entrepreneur social relations have on the mode of entrepreneurship practices